Impact of Consolidative Unrelated Cord Blood Transplantation on Clinical Outcomes of Patients With Relapsed/Refractory Acute B Lymphoblastic Leukemia Entering Remission Following CD19 Chimeric Antigen Receptor T Cells - Xu, Qianwen; Xue, Lei; An, Furun; Xu, Hui; Wang, Li; Geng, Liangquan; Zhang, Xuhan; Song, Kaidi; Yao, Wen; Wan, Xiang; Tong, Juan; Liu, Huilan; et al. (Frontiers in Immunology, 2022)
Background: While chimeric antigen receptor (CAR)-T cell therapy is becoming widely used in hematological malignancies with remarkable remission rate, its high recurrence remains an obstacle to overcome. The role of consolidative transplantation following CAR-T cell mediated remission remains controversial. We conducted a retrospective study to explore whether bridging to unrelated cord blood transplantation (UCBT) could improve prognosis of patients who entering remission after CAR-T therapy with different characteristics through subgroup analysis. Methods: We reviewed 53 patients with relapsed/refractory (R/R) acute B lymphoblastic leukemia (B-ALL) successfully infused with CD19 CAR-T cells and achieved complete remission (CR). 25 patients received consolidative UCBT (UCBT group) and 28 patients did not accept any intervention until relapse (non-UCBT group). Subgroup analysis on prognosis was then performed according to gender, age, number of previous relapses, tumor burden, presence of poor prognostic markers and structure of CAR. Results: Compared with the non-UCBT group, patients who underwent consolidative UCBT had better median event-free survival (EFS; 12.3 months versus 6.2 months; P=0.035) and relapse-free survival (RFS; 22.3 months versus 7.2 months; P=0.046), while no significant difference was found in overall survival (OS; 30.8 months versus 15.3 months; P=0.118). Subsequent multivariate analysis revealed that bridging to UCBT was a protective factor for RFS (P=0.048) but had no significant effect on EFS (P=0.205) or OS (P=0.541). In subgroup analysis, UCBT has an added benefit in patients with specific characteristics. Patients who experienced ≥ 2 relapses or with sustained non-remission (NR) showed a better RFS (P=0.025) after UCBT. Better EFS was seen in patients with poor prognostic markers (P=0.027). In subgroup with pre-infusion minimal residual disease (MRD) ≥ 5% or with extramedullary disease (EMD), UCBT significantly prolonged EFS (P=0.009), RFS (P=0.017), and OS (P=0.026). Patients with occurrence of aGVHD appeared to have a longer duration of remission (P=0.007). Conclusion: Consolidative UCBT can to some extent improve clinical outcomes of patients with R/R B-ALL entering remission following CD19 CAR-T therapy, especially in patients with more recurrences before treatment, patients with poor prognostic markers, and patients with higher tumor burden. The occurrence of aGVHD after UCBT was associated with better RFS.